Improving Outcomes for Families of Children With Medical Needs Known to Child Welfare: A Nurse Care Coordination Program. (May 2022) - Lilly, Anne; Cavella, Marc; Roper-Lewis, Arnesha; Weglarz, Mary; Ayala, Linda; Cirillo Lilli, Alexandra; Greene, Mollie; Colabelli, Nina; Duggan, Anne
Children known to child welfare are more likely to have poor health compared to the general population. Most children served by child welfare are served in their own homes. New Jersey implemented the Child and Family Nurse Program (CFNP) to provide nurse care coordination to address the health needs of children who remain in-home. Our study described: 1) families served by CFNP; 2) services provided to these families; and 3) family well-being outcomes. The study focused on the 304 families served by CFNP from 2016 to 2017. We used CFNP data to describe families served and services provided, and family baseline and follow-up surveys to assess change in family well-being over time. Families served by CFNP experienced improvements in family protective factors and health-related quality of life from baseline to follow-up. While more rigorous studies are needed to learn CFNP's impact, it is a promising approach that merits consideration by state child welfare leaders.